Whether there effect of the used video on group guidance services to aggressive behavior? - Hariyani, Hariyani; Syahputra, Yuda (Konselor, 2019)
This research analyzed the effectiveness of Group Guidance with Video (G2-V) services in reducing aggressive behavior of junior high school students. The approach of this research is Pre-Experiment with the design of one group pretest-posttest design. Subjects in this study were tes students (five male and five female) junior high schools in North Sumatra, used purposive sampling. The instrument used was aggressive behavior scale. Analyzed data using nonparametric statistical techniques used the Wilcoxon Signed-Ranks Test and stacking Rasch models. The results of the analysis show that there is an influence of G2-V in reducing the aggressive behavior of junior high school students in North Sumatra. Based on the findings can be used by counselors to reduce the aggressive behavior of students in junior high school I discuss further the implications of guidance and counseling services.